Corporate Social Responsibility as an element of IKEA’s successful performance in the market - Egorova, Yulia (2020)
This bachelor thesis aims to analyze the contribution of IKEA’s Corporate Social Responsibility to its successful performance in the market. The thesis comprises theoretical data on CSR, its application in Sweden, IKEA’s country of origin, and an overview of the analyzed company. By the practical data, the thesis investigates if CSR has the potential to influence the market performance of the multinational corporation.